Phantoming the Subject: Diderot, LacoueLabarthe and the actor’s paradox - Hadikoesoemo, Niki (Revista Brasileira de Estudos da Presença, 2020)
This essay takes Diderot’s claim that the actor is everything and nothing at the same time as the starting point to rethink the formation of the self. Going beyond Diderot’s paradox as a theory of acting, this article argues in favor of a deconstructive analysis of the actor’s mimetic practice, put forward by Lacoue-Labarthe, which allows us to address the ontological conditions of the interplay between possession and dispossession, nothingness and possibility, distinctiveness and malleability. This essay shows that Diderot’s indirect subversion of the distinction between passive and active mimesis underlying the performing body, problematizes the question of the subject as such.